Analyzing public interventions through the lens of experimentalism: the case of the Museum of Random Memory. Issue 4 (2nd October 2019) - Markham, Annette N.; Pereira, Gabriel
ABSTRACT: Over 30 computational scientists, designers, artists, and activists collaboratively performed eight Museum of Random Memory workshops and exhibitions from 2016 to 2018. Here, we explore how the framework of 'experimentation' helped us analyze our own iterative development of techniques to foster critical data literacy. After sketching key aspects of experimentation across disciplines, we detail moments within where researchers tweaked, observed, tested, reflected, and tweaked again. This included changing scale, format, and cultural context; observing how people responded to digital versus analog memory-making activities; modifying prompts to evoke different conversations among participants about how future memories might be imagined or read by future archeologists; and finding creative ways to discuss and trouble ethics of data sharing. We conclude that coopting some of the techniques typical in natural science laboratories can prompt scholar activists to continuously recalibrate their processes and adjust interactions as they build pedagogical strategies for fostering critical data literacy in the public sphere.